IONIC LIQUIDS MATERIAL AS MODERN CONTEXT OF CHEMISTRY IN SCHOOL (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
One way to improve students’ chemistry literacy which is demanded in the modernization of modern technology-based chemistry learning is by studying ionic liquids. Low level of scientific literacy of students in Indonesia as revealed in the PISA in 2012 was the main reason of the research. Ionic liquids-based technology are necessary to be applied as a context for learning chemistry because: (1) the attention of the scientific an technology community in the use of ionic liquids as a new generation of green solvent, electrolyte material and fluidic engineering in recent years becomes larger, in line with the strong demands of the industry for the provision of new materials that are reliable, safe, and friendly for various purposes; (2) scientific explanations related to the context of the ionic liquid contains a lot of facts, concepts, principles, laws, models and theories can be used to reinforce the learning content as a media to develop thinking skill (process/competence) as demanded by PISA; (3) The modern technology-based ionic liquid can also be used as a discourse to strengthen scientific attitude. The process of synthesis of ionic liquid involves fairly simple organic reagents, so it deserves to be included in the chemistry subject in school.